MELIHAT DARWIS, SUFI PENGEMBARA DALAM NOVEL AKUNYA DIA (2020) KARYA REZA AMIRKHANI: TINJAUAN REALISME MAGIS - Sayati, Lena; Oktarina, Dwi; Junaidi, Ahmad Syafaat (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
Darwis Mustofa is a character who plays an important role in the plot of the story. Through Mustafa's character, Sufistic elements can be seen as a guide to religious teachings. The choice of a Darwis-like character as a messenger of love and advice in the storyline is inseparable from the culture of Iran and Central Asian countries where nomadic Sufi wanderers can easily be found to spread the teachings of Sufism. Therefore, this research will focus on analyzing and interpreting the Sufistic elements inherent in the character of Darwis Mustafa. To dissect the issue, this research will use an interpretative qualitative method through a magical realism approach. The data source used is Reza Amirkhani's novel Man-e-oo (2000), which has been translated into Indonesian by Bastian Zulyeno under the title Akunya Dia (2020). Sufistic elements found in the character of Darwis Mustafa include: Darwis Mustafa is present and depicted as a Sufi figure who is closely related to mysticism, has a deep meaning related to the color green, shows universality through tolerance, and represents the meaning of divine love and death in the Sufi view.